Analisis Implementasi Qanun Lembaga Keuangan Syariah dan Implikasinya Terhadap Kinerja Keuangan Bank Konversi (Studi Kasus: PT Bank Aceh Syariah) - Nurjanatin, Ririt (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the impact of the implementation of Qanun Aceh Number 11 of 2018 on the financial performance of converted banks, with a focus on PT Bank Aceh Syariah. The Qanun requires all financial institutions in Aceh to operate based on Islamic principles, thereby triggering a comprehensive conversion process of conventional banks. This transformation affects not only legal and operational aspects but also financing structures, risk management, and banking efficiency. The findings indicate that the conversion has a positive impact on financial performance, particularly in terms of liquidity, operational efficiency, and profitability. Internally, murabahah financing is proven to have a significant effect on profitability, while ijarah shows no partial effect although both are significant when analyzed simultaneously. External factors such as capital structure and bank size enhance profitability, while bank value has a negative impact and dividend policy shows no significant influence. This study confirms that the profitability of Islamic banks is determined by a combination of internal and external factors, with Qanun 11/2018 serving as a key catalyst in strengthening the stability and growth of the Islamic banking financial performance in Aceh.